High-entropy alloy coating and preparation method and application thereof

By preparing a high-entropy alloy coating with a molar ratio of Fe, Co, Cr, Ni, Al, Y, and Hf on a low-carbon steel matrix, a nano-heterophase core-shell structure is formed, which solves the problem of insufficient performance of existing high-temperature oxidation corrosion-resistant materials in extreme environments, and achieves efficient high-temperature oxidation and long-life coatings.

CN119663274APending Publication Date: 2025-03-21WUHAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411906969.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing high-temperature oxidation corrosion-resistant materials show insufficient performance in extreme environments and cannot meet the needs of practical applications.

Method used

A high-entropy alloy coating with a molar ratio of 18:18:18:36:9:0.5:0.5 was used, and the coating was prepared on a low-carbon steel matrix by laser cladding technology to form a nano-extraphase core-shell structure.

Benefits of technology

Through the design of nano-extraphase core-shell structure, this high-entropy alloy coating significantly improves the mechanical properties, thermal stability and high-temperature oxidation resistance of the coating, extends the service life of the coating, and improves its durability in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663274A_ABST
    Figure CN119663274A_ABST
Patent Text Reader

Abstract

The invention provides a high-entropy alloy coating and a preparation method and application thereof. The high-entropy alloy coating comprises Fe, Co, Cr, Ni, Al, Y and Hf according to the molar ratio of 18: 18: 18: 36: 9: 0.5: 0.5. According to the high-entropy alloy coating as well as the preparation method and the application thereof, the overall mechanical property and the thermal stability of the coating can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of alloy coatings, and in particular to a high entropy alloy coating and a preparation method and application thereof. Background Art

[0002] In recent years, scholars have successfully constructed a stable oxide barrier by introducing reactive elements (such as Y, Hf, etc.) into high entropy alloys, effectively blocking the penetration of oxygen atoms and significantly improving the core properties of the alloys, such as oxidation resistance. Huang and his team's research revealed that under 1100–1300°C, Al2O3 co-doped with Y and Hf 18 Co 30 Cr 10 Fe 10 Ni 32 Eutectic high entropy alloys, whose Al2O3 oxide layer exhibits low residual stress, low oxidation rate and no sulfur segregation, endow the alloy with excellent oxidation resistance. Lu et al. found that Y-Hf co-doped Al 1.1 CoCr 0.8 FeNi high entropy alloy exhibits extremely low oxidation rate and excellent spalling resistance at 1200℃, which is due to the highly stable nanostructure of the alloy, which promotes the uniform distribution of Y and Hf, strengthens the active element effect, and slows down the oxidation process and growth stress of the Al2O3 scale. Further research by Lu's team pointed out that Y / Ta / Hf co-doping can greatly improve the high-temperature oxidation resistance of AlCoCrFeNi high entropy alloy, mainly by increasing the Al2O3 grain size and accelerating the transformation of metastable Al2O3 to α-Al2O3. At the same time, the addition of Ta also enhances the adhesion of the coating. In addition, the study of JA Haynes et al. also explored the effect of water vapor on FeCoCrNiAlYHf coating. The results showed that the NiCoCrAl bonding layer co-doped with Y and Hf is beneficial to prolong the service life of thermal barrier coating (TBC).

[0003] Traditional high-temperature oxidation corrosion resistant materials (such as aluminum-formed austenitic (AFA) steel, heat-resistant alloys, etc.) have the ability to resist high-temperature oxidation corrosion to a certain extent, but when faced with more extreme environmental conditions (such as ultra-high temperature, highly corrosive media, etc.), their performance is often stretched and cannot meet the needs of practical applications. This situation not only reveals the gap in the current research field, but also highlights the urgency and importance of the research and development of high-performance high-temperature oxidation corrosion resistant materials. Summary of the invention

[0004] The purpose of the present invention is to provide a high entropy alloy coating and a preparation method and application thereof, which are helpful to extend the service life of the coating and improve its durability in harsh environments.

[0005] To achieve the above objectives, the present invention provides a high entropy alloy coating comprising Fe, Co, Cr, Ni, Al, Y, and Hf in a molar ratio of 18:18:18:36:9:0.5:0.5.

[0006] Preferably, the thickness of the high entropy alloy coating is 1 to 1.2 mm.

[0007] A method for preparing a high entropy alloy coating comprises the following steps:

[0008] Melting metals and metal alloys in a vacuum state or under gas protection conditions to obtain liquid metal;

[0009] The metal liquid flows downward through the heat-insulating crucible and the guide nozzle, and is atomized and broken into droplets by the high-pressure airflow through the nozzle;

[0010] The droplets solidify into spherical and sub-spherical particles in flight, and then are screened and separated to prepare metal powders of various particle sizes.

[0011] Drying the prepared metal powder to obtain high entropy alloy powder;

[0012] Select low carbon steel as the cladding substrate, and grind and clean the cladding substrate;

[0013] Placing high entropy alloy powder into a coaxial powder feeder for laser cladding;

[0014] High entropy alloy coating is prepared on the surface of cladding substrate by laser cladding technology.

[0015] Preferably, the particle size range of the high entropy alloy powder is 105-150 microns.

[0016] Preferably, the spot diameter of the laser cladding is 3 mm, the laser power is 2000-2200 W, the scanning speed is 10-15 mm / s, the powder feeding rate is 16.8-18.8 g / min, the carrier gas flow rate is 1.2-1.5 L / min, and the substrate is preheated at 250-300°C.

[0017] Preferably, the matrix also includes iron-based alloy materials (such as 45 steel, Q235 steel, stainless steel, etc.), nickel-based alloy materials (such as nickel alloy, Inconel series (such as Inconel 718, Inconel 625, etc.), Hastelloy series, etc.), titanium-based alloy materials (such as pure Ti matrix, TC4 titanium alloy, etc.).

[0018] Preferably, the inert gas cabin is used for protection, and the oxygen content in the cabin is less than 50ppm.

[0019] Preferably, the high entropy alloy coating is a nano-heterogeneous core-shell structure.

[0020] Preferably, the protective gas includes one or more inert gases such as argon and helium.

[0021] A high entropy alloy coating is used as a high-temperature anti-oxidation coating.

[0022] Therefore, the present invention adopts the above-mentioned high entropy alloy coating and its preparation method and application, and the technical effects are as follows:

[0023] (1) The nano-heterogeneous core-shell structure in the high-entropy alloy coating is an innovative design that has excellent properties endowed by a semi-coherent interface, such as extremely strong interface stability. This structural feature helps to improve the overall mechanical properties and thermal stability of the coating.

[0024] (2) The heterogeneous nano-core-shell structure is effectively enriched at the grain boundaries, which further enhances the thermal stability of the coating under high temperature conditions. This enrichment phenomenon helps to reduce defects at the grain boundaries, thereby improving the high-temperature oxidation resistance of the coating.

[0025] (3) Under high temperature conditions, the (AlNi2)@(YNi3+Cr2O3+Hf) structure in the nano-heterogeneous core-shell structure provides a three-layer oxide barrier (Cr2O3, Y2O3, Al2O3). These oxide barriers are closely arranged, effectively blocking the diffusion path of oxygen atoms, thereby significantly reducing the oxidation rate of the coating.

[0026] (4) The nano-heterogeneous core-shell structure not only enhances the structural stability of the coating, but also exhibits a significant inhibitory effect on the diffusion behavior of oxygen (O). This inhibitory effect helps to extend the service life of the coating and improve its durability in harsh environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is the SEM image of HEAs powder; Figure 1 (a) is the SEM image of HEAs powder; Figure 1 (b) Fe 18 Co 18 Cr 18 Ni 36 9Y 0.5 Hf 0.5 Particle size information of alloy powder; Figure 1 (c) Fe 18 Co 18 Cr 18 Ni 36 9Y 0.5 Hf 0.5 EDS composition information of alloy powder;

[0028] Figure 2 Fe 18 Co18 Cr 18 Ni 36 9Y 0.5 Hf 0.5 XRD spectrum of high entropy alloy coating;

[0029] Figure 3 HEAs coated with Fe 18 Co 18 Cr 18 Ni 36 9Y 0.5 Hf 0.5 Cross-sectional macromorphology and EPMA element distribution; Figure 3 (a) HEAs coated Fe 18 Co 18 Cr 18 Ni 36 9Y 0.5 Hf 0.5 SEM image after chemical etching Figure 3 (b) Fe 18 Co 18 Cr 18 Ni 36 9Y 0.5 Hf 0.5 A magnified image of the part after chemical etching; Figure 3 (c) Fe 18 Co 18 Cr 18 Ni 36 9Y 0.5 Hf 0.5 EPMA (electron probe microanalyzer) element distribution map of the bonding area between the high entropy alloy (HEA) coating and the substrate;

[0030] Figure 4 TEM analysis of nano core-shell structure; Figure 4 (a) TEM micrograph of a typical nanocore-shell structure distributed at the grain boundary and the corresponding STEM-EDS elemental map; Figure 4 (b) BF-TEM image and SAED sampling area of ​​a typical nanocore-shell structure; Figure 4 (c) SAED spectrum; Figure 4 (d) is a line scan of the element distribution of a typical nano core-shell structure. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0032] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0033] Embodiment 1

[0034] A method for preparing a high entropy alloy coating comprises the following steps:

[0035] According to the HEA powder combination in Table 1, metals and metal alloys are melted in a vacuum state or under gas protection conditions to obtain metal liquid;

[0036] The metal liquid flows downward through the heat-insulating crucible and the guide nozzle, and is atomized and broken into droplets by the high-pressure airflow through the nozzle;

[0037] The droplets solidify into spherical and sub-spherical particles in flight, and then are screened and separated to prepare metal powders of various particle sizes.

[0038] Drying the prepared metal powder to obtain high entropy alloy powder;

[0039] Select low carbon steel as the cladding substrate, and grind and clean the cladding substrate;

[0040] Placing high entropy alloy powder into a coaxial powder feeder for laser cladding;

[0041] High entropy alloy coating was prepared on the surface of cladding substrate by laser cladding technology. IPG's YLS-4000 laser was used for laser cladding. The spot diameter of laser cladding was 3mm. KUKA 6-axis robot was used for four-way coaxial powder feeding. The laser power was 2000W, the scanning speed was 10mm / s, the powder feeding rate was 16.8g / min, the carrier gas flow rate was 1.2L / min, the substrate was preheated to 250℃, and the inert gas cabin was used for protection. The oxygen content in the cabin was <50ppm.

[0042] Table 1 HEAs powder composition

[0043] Sample Fe Co Ni Cr Al Y Hf FeCoCrNiAlYHf 17.40 18.46 38.47 16.19 8.48 0.51 0.49

[0044] Embodiment 2

[0045] Table 2 HEAs powder composition

[0046] Sample Fe Co Ni Cr Al Y Hf FeCoCrNiAlYHf 17.40 18.46 38.47 16.19 8.48 0.45 0.55

[0047] The preparation method of Example 1 is retained, and a high entropy alloy coating is prepared according to the formula in Table 2.

[0048] Embodiment 3

[0049] Table 3 HEAs powder composition

[0050] Sample Fe Co Ni Cr Al Y Hf FeCoCrNiAlYHf 17.40 18.46 38.47 16.19 8.48 0.55 0.45

[0051] The preparation method of Example 1 is retained, and a high entropy alloy coating is prepared according to the formula in Table 3.

[0052] Analysis of Example 1, Example 2 and Example 3

[0053] Strength and hardness: The formulations in the three groups of examples all exhibit high strength and hardness because the contents of the main elements Fe, Co, Cr, and Ni are relatively high.

[0054] Corrosion resistance: Due to the moderate and consistent Al content, the corrosion resistance of the formulations in the three groups of examples is excellent and comparable.

[0055] Rare earth element effect: When the Y content is 0.51%, it is more conducive to grain refinement and corrosion resistance improvement, because the appropriate amount of Y can better play its role in grain refinement and forming a dense oxide film. When the Y content is reduced to 0.45%, although it can still play a certain role, it is not as significant as when it is 0.51%.

[0056] When the Hf content is 0.49%, it is more conducive to improving the hardness and wear resistance of the alloy, because the right amount of Hf can form a fine hard phase. When the Hf content increases to 0.55%, it tends to improve the high temperature stability and oxidation resistance of the alloy. However, too high Hf content may also lead to increased alloy cost and increased processing difficulty.

[0057] Analysis of the results of Example 1

[0058] Before the experiment, the samples were cut into 10mm×10mm×5mm specifications using a wire cutting machine for microstructural characterization and performance testing. Then the coating surface was ground with sandpaper of 400, 800, 1000, 1500, 2000, and 3000 mesh in order, and finally the samples were mechanically polished with diamond spray (particle size 0.5μm). After the samples were polished, they were rinsed with deionized water (pH=5.6~5.8) and alcohol, and dried with hot air. After the samples were corroded with aqua regia (V(HCl):V(HNO3)=3:1) for 30s, the microstructural evolution of all samples was observed by Gemini SEM 360 thermal field emission scanning electron microscope (FE-SEM). The structure of the samples was characterized by X-ray diffractometer (XRD, D / MAX2500PC), using Cu target Kα radiation for testing, with a scanning speed of 4° / min, a scanning step of 0.02°, an accelerating voltage of 40 kV, a current of 40 mA, and a diffraction angle of 0° to 90°. Conventional TEM and high-resolution electron microscopy (HREM) observations were performed using a Hitachi H-800TEM microscope equipped with an energy dispersive spectrometer (EDS) with an accelerating voltage of 200 kV and a JEOL JEM-ARM200F / UHR electron microscope operating at 200 kV to study the Fe 18 Co18 Cr 18 Ni 36 9Y 0.5 Hf 0.5 Microstructure of the samples.

[0059] Figure 1 (a) shows the SEM image of HEAs powder. Figure 1 (b) shows Fe 18 Co 18 Cr 18 Ni 36 9Y 0.5 Hf 0.5 The particle size information of the alloy powder shows that the particle size range is 105-150 microns. Figure 1 (c) shows Fe 18 Co 18 Cr 18 Ni 36 9Y 0.5 Hf 0.5 EDS composition information of alloy powder.

[0060] Figure 2 Fe 18 Co 18 Cr 18 Ni 36 9Y 0.5 Hf 0.5 The XRD spectrum of the high entropy alloy coating proves that the prepared high entropy alloy coating has successfully formed a stable solid solution structure. As can be seen from the figure, according to the PDF card file (PDF, FeCoCrNi: #35-1489), the high entropy alloy coating forms a face-centered cubic (FCC) stable solid solution with obvious characteristic peaks.

[0061] Figure 3 (a) and Figure 3 (b) shows the HEAs-coated Fe 18 Co 18 Cr 18 Ni 36 9Y 0.5 Hf 0.5 SEM images after chemical etching and local magnified images. After strong aqua regia corrosion, the intergranular phase on the metal surface remains stable, with no obvious signs of dissolution or damage, indicating that the HEAs coating Fe 18 Co 18 Cr 18 Ni 36 9Y 0.5 Hf 0.5 The intergranular phase in the alloy has higher chemical stability and corrosion resistance.

[0062] Figure 3 (c) The Fe 18 Co 18 Cr 18 Ni 36 9Y 0.5 Hf 0.5 EPMA (Electron Probe Microanalyzer) element distribution diagram of the bonding area between the high entropy alloy (HEA) coating and the substrate. The hierarchical structure of the HEA coating along the cross section is the laser cladding zone, the heat-affected zone, and the fusion line (FL) to the substrate. There are no significant defects in the fusion line area, such as pores and cracks. This discovery strongly proves that an extremely strong metallurgical bond is achieved between the coating and the substrate.

[0063] Figure 4 (a)-(d) show the Fe 18 Co 18 Cr 18 Ni 36 9Y 0.5 Hf 0.5 TEM and STEM-HADF images of nanocore-shell structures at grain boundaries in high entropy alloys. Figure 4 (a) and Figure 3 (c) clearly shows the distribution of nano-core-shell structures at the grain boundaries, Figure 4 (a) It can be seen that the shell of the core-shell structure is rich in Y, Ni, Cr, O and a small amount of Hf precipitation. This multi-composite structure not only enhances the stability of the shell, but also has a positive effect on the oxidation resistance and thermal stability of the alloy. The core of the nano-core-shell structure is composed of Al and Ni, forming a stable AlNi2 metal compound phase.

[0064] Figure 4 The SAED pattern analysis in (b) further verifies the chemical composition of the core-shell structure. The pattern diffraction results in the SAED-1 region clearly indicate the AlNi2 phase in the core, while the SAED-2 region reveals a complex structure of the shell composed of YNi3 intermetallic compounds and Cr2O3 oxides. This composite shell not only improves the stability of the alloy, but may also affect the overall performance of the alloy through its unique interface effect.

[0065] at last, Figure 4The element distribution line scan results in (d) not only intuitively show the significant difference in element content between the shell and the core area, but also further confirm the specific ratio of Ni to Y in the shell (Ni mass fraction is three times that of Y), which is consistent with the formation of YNi3 phase. At the same time, the coexistence of Cr oxides in the shell further emphasizes the complexity and versatility of the structure. The ratio of Ni to Al in the core (Ni mass fraction is three times that of Al) directly supports the existence of AlNi2 phase, which is consistent with the SAED analysis results.

[0066] Therefore, the present invention adopts the above-mentioned high entropy alloy coating and its preparation method and application, which helps to improve the overall mechanical properties and thermal stability of the coating.

[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A high entropy alloy coating, characterized in that: The molar ratio of Fe, Co, Cr, Ni, Al, Y and Hf is 18:18:18:36:9:0.5:0.

5.

2. A high entropy alloy coating according to claim 1, characterized in that: The thickness of the high entropy alloy coating is 1 to 1.2 mm.

3. A method for preparing a high entropy alloy coating, characterized in that: The following steps are involved: Melting metals and metal alloys in a vacuum state or under gas protection conditions to obtain liquid metal; The metal liquid flows downward through the heat-insulating crucible and the guide nozzle, and is atomized and broken into droplets by the high-pressure airflow through the nozzle; The droplets solidify into spherical and sub-spherical particles in flight, and then are screened and separated to prepare metal powders of various particle sizes. Drying the prepared metal powder to obtain high entropy alloy powder; Select low carbon steel as the cladding substrate, and grind and clean the cladding substrate; Placing high entropy alloy powder into a coaxial powder feeder for laser cladding; High entropy alloy coating is prepared on the surface of cladding substrate by laser cladding technology.

4. The method for preparing a high entropy alloy coating according to claim 3, characterized in that: The particle size range of the high entropy alloy powder is 105-150 microns.

5. The method for preparing a high entropy alloy coating according to claim 3, characterized in that: The spot diameter of laser cladding is 3mm, the laser power is 2000~2200W, the scanning speed is 10~15mm / s, the powder feeding rate is 16.8~18.8g / min, the carrier gas flow rate is 1.2~1.5L / min, and the substrate is preheated at 250~300℃.

6. The method for preparing a high entropy alloy coating according to claim 3, characterized in that: The matrix also includes: iron-based alloy material, nickel-based alloy material, and titanium-based alloy material.

7. The method for preparing a high entropy alloy coating according to claim 3, characterized in that: Inert gas cabin protection, oxygen content in the cabin is <50ppm.

8. The method for preparing a high entropy alloy coating according to claim 3, characterized in that: The high entropy alloy coating is a nano-heterogeneous core-shell structure.

9. The method for preparing a high entropy alloy coating according to claim 3, characterized in that: The shielding gas includes one or more inert gases such as argon and helium.

10. Application of a high entropy alloy coating as a high-temperature anti-oxidation coating.